Post-propaganda - Staal, Jonas (Netherlands Foundation for Visual Arts, Design and Architecture, 2010)
"The essay 'Post-Propaganda" was written by visual artist Jonas Staal. His argument is based on the deep-rooted relationship between art institution and politics, a relationship that goes unacknowledged by both parties. The art institution refuses to question its supposed autonomy and to consider the way it functions from the perspective of socio-economic interests. Conversely, politics refuses to give up its untenably neutral position with respect to the arts. Politics persists in the ideal of a 'free' and 'independent' art, in spite of its far-reaching and direct interference in both funding and content. In doing so, politics denies its direct responsibility and power as the actual commissioning client of the art institution. The central question of this essay considers the precise nature of the political interests that bring about its involvement with the arts. It also asks how art currently functions as a means of political propaganda. What are the ideological foundations that contemporary art is supposed to portray? With this manifesto, Jonas Staal aims to further the discussion about art and politics. He calls for a truly politicised art and an artification of politics. His goal is to oblige both parties to publicly re-appropriate and propagate the power over the formation, experience and execution of democracy." -- Provided by publisher.